Liquid‐Phase Synthesis of 2′‐Methyl‐RNA on a Homostar Support through Organic‐Solvent Nanofiltration. Issue 26 (26th May 2015) - Gaffney, Piers R. J.; Kim, Jeong F.; Valtcheva, Irina B.; Williams, Glynn D.; Anson, Mike S.; Buswell, Andrew M.; Livingston, Andrew G.
Abstract Due to the discovery of RNAi, oligonucleotides (oligos) have re‐emerged as a major pharmaceutical target that may soon be required in ton quantities. However, it is questionable whether solid‐phase oligo synthesis (SPOS) methods can provide a scalable synthesis. Liquid‐phase oligo synthesis (LPOS) is intrinsically scalable and amenable to standard industrial batch synthesis techniques. However, most reported LPOS strategies rely upon at least one precipitation per chain extension cycle to separate the growing oligonucleotide from reaction debris. Precipitation can be difficult to develop and control on an industrial scale and, because many precipitations would be required to prepare a therapeutic oligonucleotide, we contend that this approach is not viable for large‐scale industrial preparation. We are developing an LPOS synthetic strategy for 2′‐methyl RNA phosphorothioate that is more amenable to standard batch production techniques, using organic solvent nanofiltration (OSN) as the critical scalable separation technology. We report the first LPOS‐OSN preparation of a 2′‐Me RNA phosphorothioate 9‐mer, using commercial phosphoramidite monomers, and monitoring all reactions by HPLC, 31P NMR spectroscopy and MS.